2022
DOI: 10.1097/hjh.0000000000003100
|View full text |Cite
|
Sign up to set email alerts
|

Increased mortality with intensive control in patients with higher baseline SBP and lower Framingham risk

Abstract: Objective: In the Systolic Blood Pressure Intervention Trial (SPRINT), the relative reduction in primary outcome with intensive blood pressure (BP) control was numerically smallest in the highest baseline SBP tertile. In this post hoc analysis of SPRINT, the goal was to explore whether the effects of intensive BP treatment varied among patients with different baseline SBP and cardiovascular risks.Methods: Patient-level data from 9361 randomized participants in SPRINT were used. Heterogeneity between treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Finally, a post hoc analysis of the SPRINT for patients with higher baseline BP at enrolment and without other traditional CV risk factors (which may be the case with younger patients with CKD), lower target BP was associated with increased risk of death [31]. J curve phenomenon-increased CV mortality at very high and low BP is described in the general population as well as in CKD [32].…”
Section: Intensive Bp Control May Be Harmfulmentioning
confidence: 99%
“…Finally, a post hoc analysis of the SPRINT for patients with higher baseline BP at enrolment and without other traditional CV risk factors (which may be the case with younger patients with CKD), lower target BP was associated with increased risk of death [31]. J curve phenomenon-increased CV mortality at very high and low BP is described in the general population as well as in CKD [32].…”
Section: Intensive Bp Control May Be Harmfulmentioning
confidence: 99%
“…It is worth mentioning that we should be more cautious when generalizing the results from SPRINT. For the elderly whose life expectancy is less than one year, with low Framingham risk score and high baseline SBP (at least 160 mmHg), intensive SBP treatment may not be a good choice ( 14 , 15 ). Some observational studies suggested the cautious application of SBP less than 130 mmHg and observed a U or J shape relationship between BP and all-cause mortality ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%